A novel SPINK5 donor splice site variant in a child with Netherton syndrome. Issue 3 (3rd February 2021) - Mintoff, Dillon; Borg, Isabella; Vornweg, Julia; Mercieca, Liam; Merdzanic, Rijad; Numrich, Johannes; Aquilina, Susan; Pace, Nikolai Paul; Fischer, Judith
Abstract: Background: Netherton syndrome (NS) is a genodermatosis caused by loss‐of‐function mutations in SPINK5, resulting in aberrant LEKTI expression. Method: Next‐generation sequencing of SPINK5 (NM_001127698.1) was carried out and functional studies were performed by immunofluorescence microscopy of a lesional skin biopsy using anti‐LEKTI antibodies. Results: We describe a novel SPINK5 likely pathogenic donor splice site variant (NM_001127698.1:c.2015+5G>A) in a patient with NS and confirm its functional significance by demonstrating complete loss of LEKTI expression in lesional skin by immunofluorescence analysis. Conclusion: The 2015+5G>A is a novel, likely pathogenic variant in NS. Herein we review and assimilate documented SPINK5 pathogenic variants and discuss possible genotype–phenotype associations in NS. Abstract : We present a novel SPINK5, likely pathogenic mutation in a patient with Netherton syndrome of Maltese‐Caucasian ethnicity. We also tabulate the spectrum of documented SPINK5 mutations in this genodermatosis and discuss potential genotype–phenotype associations.